e-Banking usage by generations X, Y, and Z - Rodrigues, L. F.; Oliveira, A.; Rodrigues, H. (Application of Emerging Technologies (AHFE 2023), 2023)
Without considering the demands of the customers, banks hurried to face-lift their front-end design and offer non-essential services. This recent attitude has harmed a good digital banking experience, and consequently the adoption of e-banking. To have a clear vision of how banks can stand out in a digital transformation 634 e-banking users were interviewed from the generations X, Y, and Z. A qualitative analysis was conducted using Leximancer software, to determine similarities and differences in three generations’ attitudes toward digital banking. The ﬁndings highlighted nineteen concepts grouped into eight key themes, namely: transfers, availability, use, speed, information, price, complex(city), and market. Users of digital banks value the ease of accessibility of services and operations in the ﬁnancial market, manage their accounts and savings, they are worried about pricing, speed of transfers, and product infor- mation. While Gen X (the elder generation) focuses on digital banking primarily for the services it offers, Gen Y (the middle generation) uses it to gather information on ﬁnancial markets and for bank operations from anywhere, and Gen Z (the younger generation) just uses banking for transfers. This study helps to understand how digi- tal banking is adopted by proposing a new conceptual. This study helps to understand how digital banking is used by different generations and proposes a new concep- tual map to describe what factors are most crucial for each Generation X, Y, and Z in adopting digital banking strategies.